Orange-fleshed sweetpotato puree for baked and fried products in Kenya, Malawi and Uganda. Project profile. - International Potato Center (International Potato Center, 2019)
Orange-fleshed sweetpotato (OFSP) puree can be used as a substitute for 30-60% of the flour in a range of baked or fried products, reducing production costs and increasing their nutritional content. International Potato Center (CIP) scientists developed a vacuum-packed storage technology that allows OFSP puree to be stored without refrigeration for months, creating the potential for widespread use by bakeries and food vendors. This project aims to take the OFSP puree for bakery application to scale in Kenya, Malawi and Uganda.